Effects Of Turmeric Oil As A Dietary Supplements on The Growth Performance and Carcass Characteristics of Broiler Chickens - Oluwafemi, R. A; Uankhoba, I. P; Alagbe, J.O (International Journal on Orange Technologies, 2021)
An experiment was carried out to study the effect of turmeric oil as a dietary supplement on the growth performance, carcass characteristics and blood profile of broiler chickens. Two hundred one-day-old commercial broiler chicks (Arbo acre) were reared in a deep litter poultry house and divided into five groups of forty (40) birds each. The groups were assigned to five dietary treatments each of the treatments had four replicates consisting of 10 birds each in a Completely Randomized Design. Basal diet was formulated to meet the nutritional requirement of birds according to NRC (1994). Treatment 1 (T1) contained basal diet with 0 % turmeric oil (TOL), while T2, T3, T4 and T5 were fed diet supplemented with TOL at 0.1 %, 0.2 %, 0.3 % and 0.4 % respectively. The experiment lasted for 8 weeks during and the data obtained were used to evaluate the average daily weight gain (ADWG), average total feed intake (AFTI), mortality and relative organ /carcass weights. Significant differences (P<0.05) were recorded in the ADWG, ADFI and feed conversion ratio among the treatments. The relative weights of the organs and dressing percentage were significantly (P<0.05) influenced across the treatments. It was concluded that turmeric oil contains several bioactive chemicals which confers it the ability to perform multiple biological functions and its supplementation at 0.4 % does not have any deleterious effect on the general performance of the animal.